Increasing frequency of bite wounds with increasing population density in Eurasian badgers, Meles meles - MacDonald, D; Harmsen, B; Johnson, P; Newman, C (2004)
Eurasian badgers sometimes live in territorial, mixed-sex groups; the adaptive significance of this is not understood, but members generally interact amicably. None the less, badgers occasionally fight and inflict sometimes severe wounds on one another. Based on 498 badger life histories, from first emergence as a cub until death, documented during a 10-year trapping study at Wytham Woods, Oxfordshire, U.K., the patterns and rates of bite wounding and consequential scarring were examined. Male badgers received more wounds and more severe wounds than did females. Wounding rates for both sexes increased significantly with age, and there was evidence that heavier individuals received most wounds. No seasonal pattern in wounding rates was apparent. During the study, the badger population size increased three-fold and wounding rates, particularly in males, showed a density-dependent increase. The rate of bite wounding increased with group size, and this increase was more marked among males than among females. Among males, but not females, the rate of bite wounding also increased with the number of badgers living in adjoining territories. © 2004 The Association for the Study of Animal Behaviour. Published by Elsevier Ltd. All rights reserved.